(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article explores the significance of religious and secular balance in society. It analyzes the historical development of religious and secular values, their role in modern society, and the importance of their harmony in preventing extremism and radicalism. The example of Uzbekistan illustrates the integration of these principles.